TikTok´ s Impact on Police Training in Colombia - Fajardo Pascagaza, Ernesto; Tobón Tobón, Sergio; Cervantes Estrada, Luis Carlos (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Applications that use artificial intelligence to create content have become trends such as the TikTok platform. The objective is to analyze the influence of TikTok on the professional training of Police cadets. The method is mixed and the type of research is exploratory and analytical. For the results, a survey was applied to 590 cadets who value the use of the platform as an innovative technological tool for educational support. In conclusion, by properly using TikTok and strategically integrating its content to teach, this tool becomes a valuable aid in technological innovation.